The sleep and mental health of gifted children: A prospective, longitudinal, community cohort study. Issue 1 (2nd January 2020) - Cook, Fallon; Hippmann, Danielle; Omerovic, Emina
ABSTRACT: Prior research provides mixed findings on the prevalence of sleep problems and mental health difficulties experienced by gifted children, with findings largely based on studies of small clinical samples. In a large, prospective, longitudinal, community cohort, the current study aimed to examine parent report of child sleep problems at ages 1, 2, 3 and 11, and child mental health difficulties at ages 5, 7 and 11 years, in gifted (IQ ≥ 120; n = 192) compared to non-gifted children (IQ < 120; n = 1015). Parents completed questionnaires about their child's sleep and mental health difficulties, and children's intelligence was assessed at age 7. There were no significant differences between gifted and non-gifted children on prevalence of sleep problems at any age. Gifted children had significantly fewer symptoms of mental health difficulties than non-gifted children at multiple time points and showed 66% reduced odds for having mental health difficulties in the clinical range at 11 years of age. This study found no evidence that gifted children experience more sleep problems or more mental health difficulties than their peers during childhood.